A simple construction of 2-phenylimino-1,3-thiazolidin-4-ones - Hahn, HG; Nam, KD; Mah, H (PERGAMON-ELSEVIER SCIENCE LTD, 2001)
A new methodology for the construction of 2-phenylimino-1,3-thiazolidin-4-one skeleton is described. Reaction of maleic anhydride (5a) or maleimides (5b, 5c) with thiourea (6) gave the corresponding 2-imino-1,3-thiazolidin-4-ones (7) and (9) respectively. The reaction proceeded with high yield in polar solvents. In non-polar solvents at high temperature, however, isothiocyanate (8) was formed as a by-product presumably by the pyrolysis of thiourea (6). The proposed mechanism of the reaction was discussed.